Integrated nutrient management in scented rice and its residual effect on pea under paira cropping system - Khanda, C M; Nayak, B S; Nayak, Anshuman; Mishra, G C; Mohanty, S K; Das, S; Mandi, N; Prasad, G (ORYZA-An International Journal of Rice, 2020)
An experiment was conducted to study the effect of integrated nutrient management in scented rice and its residual effect on pea under paira cropping system at Regional Research and Technology Transfer Station (RRTTS), Bhawanipatna, Kalahandi, Odisha during 2015-16 and 2016-17. Twelve treatment combinations comprising of T1 - FYM @ 10 t ha-1 + vermicompost @ 2.5 t ha-1 + neem cake @ 2.5 q ha-1 + Azospirillum @ 5 kg ha-1 + PSM @ 5 kg ha-1, T2 - STBFR (Soil test based fertilizer recommendation 75 : 30 : 20 kg N:P2O5: K2O ha-1), T3 - STBFR + FYM @ 5 t ha-1, T4 - STBFR + Azospirillum @ 5 kg ha-1 + PSM @ 5 kg ha-1, T5 - STBFR + Zn @ 5 kg ha-1, T6- STBFR + S @ 20 kg ha-1, T7- STBFR + Zn @ 5 kg ha-1 + S @ 20 kg ha-1, T8- STBFR + FYM @ 5 t /ha + Zn @ 5 kg ha-1 + S @ 20 kg ha-1, T9 - STBFR + FYM @ 5 t ha-1 + Azospirillum @ 5 kg ha-1 + PSM @ 5 kg ha-1, T10 - STBFR + FYM @ 5 t ha-1 + Azospirillum @ 5kg ha-1+ PSM @ 5kg ha-1 + Zn @ 5 kg ha-1 + S @ 20 kg ha-1, T11 - Farmers practice (only chemical fertilizer @ 40 : 20 : 20 kg N : P2O5 : K2O ha-1), T12 - STBFR + vermicompost @ 2.5 t ha-1 were tried in RBD with three replications. The soil of the experimental site was black cotton typehaving pH- 6.11 , O.C.- 0.72 %, E.C- 0.004 (dS m-1), available N -175.9 kg ha-1 (low), available P-36.7 kg ha-1 (medium) and available K- 283.6 kg ha-1 (high). Geetanjali was the test variety for rice and Azad Pea-1 for pea. Application of STBFR (75 : 30 : 20 kg N : P2O5 : K2O ha-1) + FYM @ 5 t ha-1 + Azospirillum @ 5 kg ha-1 + PSM @ 5 kg ha-1 + Zn @ 5 kg ha-1 + S @ 20 kg ha-1 (T10) to medium duration aromatic rice (var. Geetanjali) producedhigher rice grain yield (4065 kg ha-1) and pea seed yield (1044 kg ha-1) from aromatic rice -pea paira cropping system. However, application of STBFR + FYM @ 5 t ha-1 + Zn @ 5 kg ha-1 + S @ 20 kg ha-1 producing grain yield (3944 kg ha-1) and pea seed yield 977 kg ha-1 is another option. Application of STBFR (75 : 30 : 20 kg N : P2O5 : K2O ha-1) + FYM @ 5 t ha-1 + Azospirillum @ 5 kg ha-1 + PSM @ 5 kg ha-1 + Zn @ 5 kg ha-1 + S @ 20 kg ha-1 (T10) recorded maximum gross return (Rs. 1,26,991 ha-1) , net return (Rs. 80,146 ha-1) and B : C ratio of 2.71. The increase in rice equivalent yield (REY) in this treatment was 51.4% higher than the farmer practice i,e., application of chemical fertilizers alone (40 : 20 : 20 kg N : P2O5 : K2O ha-1).